The story of Christmas : words from the Gospels of Matthew and Luke - Ray, Jane. (New York : Dutton Children's Books, 1991)
Illustrates the story of the birth of Jesus and its aftermath, adapted from the King James version of the Bible.
"Originally published 1991 in Great Britain by Orchard Books ... London"--T.p. verso.
School Library Journal, December 1995.
Publisher's Weekly, October 2010.
Booklist, May 2011.
Teacher Librarian, September 2010.
School Library Journal.
Keywords: Jesus Christ -- Nativity; Jesus Christ -- Nativity; Jesus Christ -- Nativity; Bible stories, English -- New Testament Matthew; Bible stories, English -- New Testament Luke; Bible stories -- New Testament; Bible stories; Bible stories. -- N.T. Matthew; Bible stories. -- N.T. Luke